Pressure compensation by a floppy disk in a sprinkler with rotation by centrifugal action - De Oliveira, Vinicius Mendes Rodrigues; Filho, João Alberto Fischer [UNESP]; Zanini, José Renato [UNESP]; Dias Drumond, Luis César (Universidade Estadual de Londrina, 2016)
Water wastage is a great concern worldwide. Water is effectively utilized by using equipment and systems that have more uniform water distribution. The objective of this study was to evaluate the performance of the FR Super 10 sprinkler with a pressure compensator under different pressures, spacing, and installation heights. The tests were performed in the laboratory, and pressure was controlled with two gauges calibrated with a mercury column. The distribution uniformity was measured using the Christiansen uniformity coefficient (CUC) and distribution uniformity coefficient (CUD). Four spray nozzles were utilized for the Super 10 sprinkler, at two heights (0.6 and 1.2 m), six pressures (25, 30, 35, 40, 45, and 50 m H2O), and six spacings (9 × 9, 9 × 10, 10 × 10, 9 × 12, 10 × 12, and 12 × 12 m). The blue, yellow, and red nozzles presented self-compensating features and the green nozzle was not fully self-compensating. The manufacturing coefficients of variations were lower in the nozzles with smaller apertures (blue and yellow) compared to those with larger apertures. Increasing the sprinkler height provided better water distribution uniformity and a better radial distribution profile, lowering the application rate near the sprinkler. Since this sprinkler compensates for pressure changes, pressure did not influence the sprinkler range.
Keywords: CATCH-3D; CUC; CUD; Self-compensating; Water saving